Regional grey and white matter changes in heavy male smokers. - Rongjun Yu (Public Library of Science (PLoS), 2011)
Cigarette smoking is highly prevalent in the general population but the effects of chronic smoking on brain structures are still unclear. Previous studies have found mixed results regarding regional grey matter abnormalities in smokers. To characterize both grey and white matter changes in heavy male smokers, we investigated 16 heavy smokers and 16 matched healthy controls, using both univariate voxel-based morphometry (VBM) and multivariate pattern classification analysis. Compared with controls, heavy smokers exhibited smaller grey matter volume in cerebellum, as well as larger white matter volume in putamen, anterior and middle cingulate cortex. Further, the spatial patterns of grey matter or white matter both discriminated smokers from controls in these regions as well as in other brain regions. Our findings demonstrated volume abnormalities not only in the grey matter but also in the white matter in heavy male smokers. The multivariate analysis suggests that chronic smoking may be associated with volume alternations in broader brain regions than those identified in VBM analysis. These results may better our understanding of the neurobiological consequence of smoking and inform smoking treatment.